Simulation-based training of vaginal twin delivery for experienced gynaecologists: Useful or not?. (August 2020) - Frenken, Maria W.E.; de Wit-Zuurendonk, Laura D.; Easter, Sarah Rae; Goossens, Simone M.T.A.; Oei, S. Guid
Abstract: Objective: It is important to train clinicians to maintain and optimise maternal and neonatal outcomes after vaginal twin delivery. Simulation-based training provides opportunities for training in a realistic way without harming patients. The aim of this study is to evaluate the effect of simulation-based training concerning twin vaginal delivery on knowledge and comfort of obstetrician-gynaecologists. Study design: Obstetrician-gynaecologists participated in a twin vaginal delivery simulation between March 2018 and May 2019. Simulation-based training consisted of standardized patient interviews, didactic sessions and three different simulation-based scenarios: internal podalic version and breech extraction, assisted vaginal delivery and vaginal breech delivery with problems of aftercoming head. Pre- and posttraining, participants were asked to fill out questionnaires exploring knowledge concerning vertex-vertex twin deliveries and vertex-nonvertex twin deliveries, level of comfort performing various obstetric manoeuvres and counselling on mode of delivery for women pregnant with twins. Our primary outcome of interest was a change in knowledge or comfort surrounding vaginal twin delivery after completion of the simulation-based training. Results: The estimated median number of vaginal twin deliveries performed by the participating thirty-four obstetrician-gynaecologists was 50 (IQR 20–100). Significant improvements were seen in knowledge regarding twin deliveries with vertex-nonvertex presentation (p < 0.01). In two of three questions regarding twin delivery with vertex-vertex presentation significant improvements were seen as well (p < 0.01). Before training, 40.6% of participants felt comfortable to perform internal podalic version compared to 91.2% afterwards (p < 0.01). Comfort with breech extraction increased from 69.7% to 97.1% pre- and posttraining, respectively (p < 0.01). Before training only 55.9% would strongly counsel patients towards vaginal twin delivery as opposed to 73.5% after training (p = 0.07). Conclusions: Simulation-based training results in beneficial effects on knowledge and comfort concerning vaginal twin deliveries for obstetrician-gynaecologists. This training suggested a potential impact on provider practice with a more favourable attitude towards twin vaginal birth.